Additive manufacturing of high value Ti components: opportunities and challenges. (2017) - Chen, Jing; Ma, Chaoli; Williams, James Case
This paper describes and discusses additive manufacturing (AM) and compares it with conventional subtractive manufacturing (SM). AM creates a new way to make high values components and some resulting opportunities are described. However, like any game changing technology, there also are supporting capabilities that need to be developed or at least adapted to support implementation of the new technology. These needs also have been discussed as challenges. The availability of these will necessarily occur on varying time scales and this also is discussed. The paper ends with a simple, but optimistic long term vision for AM.